Contentious Da’wah: Response Towards the Spreading of Puritan Islamic Movement - Jinan, Mutohharun; Sudarno, Sudarno (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2019)
This articleexamines the development of the puritan Islamicmovement at Surakarta mainly is Majelis Tafsir Al-Quran (MTA).MTA is one of religious movement in Indonesia that is developed atvillages area. When this movement is developing into variousregions, then there tends to be conflict. The first purpose of thisresearch is how do Muslims respond to the expansion of MTA invarious regions. Second, what are the efforts taken by its members tomaintain their existence and continue their missions to be acceptedby the community. Even though get refusing but this movement is stillsurvive. There are four kinds of responds towards da’wah by MTA,mainly; accommodative, critical, resistant, and conflict. MTA as theminority movement doing effort, interaction andbuild up socialrelationship anddefend itself through many ways, such as; insideideology strengthening, enlarging the link of majority movementleaders, doing social jobs, leading law enforcement in completingproblem.The various ways taken by the puritan Islamic movement arestill incomplete to build good relations, and are still considered tocause problems in the society. The spreading of puritan Islamicmovement as a contentious da’wah.